Macroscopic and dermoscopic evaluation used to differentiate subungual haemorrhage from melanocytic lesions - Amanda Oakley; Mirain Phillips (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONSubungual haemorrhage describes blood located between the nail matrix and nail plate caused by trauma. Lack of recalled trauma and long duration of nail pigmentation results in specialist referrals to rule out malignant pathology. AIMThis report aims to describe the macroscopic and dermoscopic characteristics of subungual haemorrhage and to highlight its clinical differentiation from melanocytic lesions. METHODSNinety-eight nails were assessed. Pigmentation in fifty-nine was due to subungual haemorrhage and was melanocytic in the remainder (identified by a longitudinal pigmented band). RESULTSPigmentation in subungual haemorrhage had a clear proximal margin (73%) and the dermoscopic pattern was homogenous (97%), globular (78%) or streaky (34%). Features included peripheral fading (68%) and periungual haemorrhage (5%). Malignancy could be excluded in these cases by careful clinical evaluation. DISCUSSIONA combination of macroscopic and dermoscopic characteristics help make a confident diagnosis of subungual haemorrhage. A two-stage process can aid clinical diagnosis by looking for known features of subungual haemorrhage and identifying absence of malignant features.